Competency assessment in initial teacher training in physical education: a systematic review - Hinojosa-Torres, Claudio (2024)
Introduction: Competency assessment in physical education teacher education is fundamental to develop essential skills in professional practice. These competencies include technical knowledge, practical skills and a comprehensive approach that encompasses pedagogical and ethical dimensions. The diversity in competencies reflects the plurality of approaches adopted by higher education institutions, which prioritize different areas to respond to the demands of the current school system. Objective: Analyze the types of competencies assessed during physical education teacher training. Method: A systematic review was conducted following the PRISMA statement, covering articles in WoS, Scopus, Sportdiscus and ERIC databases, until July 2024. Studies were selected according to specific inclusion criteria. Results: Of a total of 820 studies identified, 38 met the inclusion criteria and were classified into seven main categories: a) Communication competencies; b) Technological and digital competencies; c) Didactic and pedagogical competencies; d) Personal and socioemotional competencies; e) Inclusion and adaptation to diverse contexts competencies; f) Professional identity and ethics competencies; and g) Evaluative and feedback competencies. Conclusion: The prioritization of pedagogical and socioemotional competencies in the training of physical education teachers fosters a comprehensive approach that generates a balanced and adaptable training, promoting effective performance in diverse educational contexts.